ANALISIS PEMANFAATAN SISTEM INFORMASIAKADEMIK UNTUK MENINGKATKAN KUALITAS SISTEM MENGGUNAKAN STANDAR ISO 9126 - Abdul Haris Muhammad; Bayu Ajisaputro; Sakinah Sudin (Program Studi Pendidikan Teknologi Informasi, 2022)
North Maluku Muhammadiyah University is one of the universities that uses an integrated system with information technology. One of the web-based systems owned by the University of Muhammadiyah North Maluku is the academic information system (SIAK). Currently, the campus academic information system has used the ISO 9001:2015 standard. ISO 9001 which is one of the international standards that regulates focus on user communities and quality management with seven defined characteristics, namely, customer focus, leadership, people involvement, process approach, evidence improvement based on decisions made, relationship management, the National Standardization Body (National Standardization Body). BSN). One way to measure system quality is to use the ISO/IEC 9126 standard. ISO/IEC 9126 is an international standard in measurement and evaluation published by the International Organization for Standardization (International Organization for Standardization) or ISO for short. ISO 9126 is the result of the development of ISO 9001. ISO 9126 is the most complete quality model and has a better analysis than other quality models. There are six characteristics of ISO 9126, namely functionality, reliability, usability, efficiency, maintainability, and portability. In this study, the researcher only analyzed three characteristics that were chosen to be used in analyzing the quality of the system under study